Introduction à l'histoire du Buddhisme Indien - Burnouf, Eugène (Cambridge library collection. Perspectives from the Royal Asiatic Society, 1844)
Eugène Burnouf (1801–52), an eminent French orientalist and scholar of Sanskrit, made groundbreaking contributions to the knowledge of Zoroastrianism and to the deciphering of the Zend and Pāli languages. He was a member of the Académie des Inscriptions et Belles-Lettres, and of numerous Asiatic societies throughout Europe. When he first published this monumental work of scholarship in 1844, Burnouf established European Buddhist studies on solid foundations. In it, he presents the Indian historical context in which Buddhism developed, as well as its connections and debates with Brahmanism. He also sheds light on the role of the caste system in this religion. To this day, Burnouf's pioneering vision continues to shape our understanding of Buddhism. This second edition was published posthumously in 1876, with an introduction by the French philosopher and journalist Jules Barthélemy Saint-Hilaire (1805–95). It remains of relevance to students of religion, oriental studies and Indian history